2015
DOI: 10.1007/s40831-014-0006-0
|View full text |Cite
|
Sign up to set email alerts
|

Product-Centric Simulation-Based Design for Recycling: Case of LED Lamp Recycling

Abstract: This paper will illustrate how a product-centric simulation approach to recycling is core to Design for Recycling (DfR) & Design for Resource Efficiency. This approach is underpinned by rigorous recycling rate calculations, building on the extensive expertise, knowhow and tools of classical minerals, and metallurgical processing. Process simulation and design tools such as the commercial HSC Sim software are applied to quantify critical DfR rules for a particular product as well as to quantify the recycling ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 24 publications
0
54
0
Order By: Relevance
“…In order to be able to achieve the quantification and the digitalization of the m-IoT, various research and [11,[42][43][44] development will be required, as reflected by Pillars 1 through 3 in Figure 4, all embedded and embraced in sustainability (social, economic, and environmental). Also of importance is the development of analysis tools and sensors that can be used to calibrate the unit models from industrial materials, recyclates, residues, scrap, etc.…”
Section: B Definition Of M-iotmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to be able to achieve the quantification and the digitalization of the m-IoT, various research and [11,[42][43][44] development will be required, as reflected by Pillars 1 through 3 in Figure 4, all embedded and embraced in sustainability (social, economic, and environmental). Also of importance is the development of analysis tools and sensors that can be used to calibrate the unit models from industrial materials, recyclates, residues, scrap, etc.…”
Section: B Definition Of M-iotmentioning
confidence: 99%
“…However, most flow sheets in environmental analysis do not consider or simplify the preceding detail. We considered these aspects, for example, in detail for lead, [43,47,50] zinc, [43,47,50] and copper flow sheets, [11,42] including their optimization and industrial understanding. (8) The quality of the recyclate streams ultimately determines in which processing steps of the complex flow sheet ( Figure 9) [39] these materials can be economically processed to metals, high-quality materials, or energy.…”
Section: F Optimization and Quantification Of The Ce Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a study is important as the metals within LED lighting products are a major source of environmental impacts. Along with Van Schaik, Reuter showed that the recycling potential for a product depends heavily on the types of materials used, how they are combined, and the available recycling technology [26]. They further encourage the research community to conduct context-specific analyses rather than generic analysis as changes in product design and the recycling system can lead to significant differences in material recovery [26].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, research on the further treatment of the PCA to separate metals from organics as well as alternative metallurgical recovery methods for PCA has been carried out (Kasper et al, 2011;Yamane et al, 2011). When considering a broader holistic approach to the research on WEEE, valuable research on modelling of WEEE treatment focusing on overall recovery of different elements has been extensively carried out by van Schaik and Reuter (2010Reuter ( , 2012Reuter ( , 2014 and Reuter and van Schaik (2015). In addition, the behaviour of precious metals in the mechanical treatment of different small electronic appliances has been studied .…”
Section: Introductionmentioning
confidence: 99%